Sharing of Clinical Trial Data and Samples: The Cancer Patient Perspective - Broes, Stefanie; Verbaanderd, Ciska; Casteels, Minne; Lacombe, Denis; Huys, Isabelle (Frontiers in Medicine, 2020)
Introduction: Today, many initiatives and papers are devoted to clinical trial data (and to a lesser extent sample) sharing. Journal editors, pharmaceutical companies, funding agencies, governmental organizations, regulators and clinical investigators have been debating the legal, ethical and social implications of clinical data and sample sharing for several years. However, only little research has been conducted to unveil the patient perspective. Aim: To substantiate the current debate, we aimed to explore the attitudes of patients towards the re-use of clinical trial samples and data and to determine how they would prefer to be involved in this process. Materials & Methods: Sixteen in-depth interviews were conducted with cancer patients currently participating in a clinical trial. Results: This study indicates a general willingness of cancer patients participating in a clinical trial to allow re-use of their clinical trial data and/or samples by the original research team, and a generally open approach to share data and/or samples with other research teams, but some would like to be informed in this case. Despite divergent opinions about how patients prefer to be engaged, ranging from passive donors up to those explicitly wanting more control, participants expressed positive opinions towards technical solutions that allow indicating their preferences. Conclusion: Patients were open to sharing and re-use of data and samples to advance medical research but opinions varied on the level of patient involvement and the need for re-consent. A stratified approach for consent that allows individualization of data and sample sharing preferences may be useful, yet the implementation of such an approach warrants further research.